Banks and remedies - Blair, William; Queen Mary College (University of London).; London Institute of International Banking, Finance and Development Law. (London : Lloyd's of London Press, 1999)
This text looks at the options that the law provides for banking, both domestically and internationally. It also explains the various opportunities available to reduce risk and organize and administer rescue packages for ailing institutions.
Includes index.
At centre of t.p: "Published jointly with the Centre for Commercial Law Studies and the London Institute of International Banking, Finance and Development Law".
oif 23/02/15
Loan
Keywords: Banking law; Remedies (Law); Banks and banking, International